Assessment of the Depth of Clinically Detected Approximal Caries Lesions Using Digital Imaging Fiber-Optic Transillumination in Comparison to Periapical Radiographs - Auste Antipoviene; Monika Girijotaite; Egle Aida Bendoraitiene (eJournal of Oral Maxillofacial Research)
Objectives: The aim of present prospective clinical trial was to assess the depth of clinically detected approximal caries lesions using digital imaging fiber-optic transillumination in comparison to periapical radiographs.